2012
DOI: 10.1111/j.1468-3083.2012.04598.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of dermokine in skin disorders

Abstract: These results provide novel insights into the physiological and pathological significance of dermokine in the epidermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
(64 reference statements)
1
28
0
Order By: Relevance
“…In a recent work, Hasegawa et al reported that Dmkn b and c are induced during early stages of wound healing in mice (Hasegawa et al, 2013b). We confirmed the induced expression of these Dmkn at day 3 post-wounding.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In a recent work, Hasegawa et al reported that Dmkn b and c are induced during early stages of wound healing in mice (Hasegawa et al, 2013b). We confirmed the induced expression of these Dmkn at day 3 post-wounding.…”
Section: Discussionsupporting
confidence: 77%
“…In the epidermis, DMKN b and c are secreted by the lamellar bodies and detected in the intercellular space between the granular and the cornified layers of normal human epidermis (Toulza et al, 2006). There is little data about DMKN expression in human diseases; DMKN b and c are overexpressed in inflammatory skin diseases, downregulated in skin cancers and, although hardly detected in normal colon epithelium, overexpressed in colorectal tumors (Hasegawa et al, 2013b;Tagi et al, 2010;Toulza et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokines such as interleukin-1b, interleukin-12, and tumor necrosis factor-a augmented dermokine expression in cultured human keratinocytes. In contrast, growth factors including epidermal growth factor, insulin-like growth factor-I, keratinocyte growth factor, and transforming growth factor-a significantly reduced dermokine expression [9]. The present study was conducted to reveal the physiological significance of dermokine-b in the epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the expression levels of dermokineb were increased in inflammatory skin disorders, while decreased in skin cancers [9]. Proinflammatory cytokines such as interleukin-1b, interleukin-12, and tumor necrosis factor-a augmented dermokine expression in cultured human keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…MMP10-dependent processing of DMKN is of particular interest, because DMKN expression in skin wounds spatially and temporally overlaps with increased levels of MMP10 in wound edge keratinocytes (4,(73)(74)(75). Moreover, recombinant DMKN inhibited ERK phosphorylation in cultured keratinocytes and delayed wound closure in mice (75,76).…”
Section: Discussionmentioning
confidence: 99%